Utilization of Skimmed Coconut Milk as a Substrate Mixture in Making Nata de Coco with Different Sugar Contents - Elfani Devitasari; Ahmad Zamroni; Nur Rizqi Bariroh; Andi Lisnawati; Muh Yamin; Elisa Ginsel Popang (Jurusan Pertanian Politeknik Pertanian Negeri Samarinda Kampus Sei Keledang Jalan Samratulangi, Kotak Pos 192 Samarinda 75123, 2024)
Skimmed coconut milk is a by-product of the coconut processing industry which is still underutilized. Apart from being worthless, skimmed coconut milk that is thrown into the environment can cause pollution. Therefore, innovation is needed so that skimmed coconut milk can be utilized into a product with high selling value. One product that can be produced by utilizing skimmed coconut milk is nata de coco. This research aims to analyze the effect of differences in sugar content contained in the substrate mixture of skimmed coconut milk and coconut water (50:50) on the yield, thickness and sensory properties of the nata de coco produced. The research design used in this study was a Completely Randomized Design (CRD), with 1 treatment factor, namely differences in sugar content (P1 = sugar content 2.5%, P2 = 7.5%, P3 = 12.5%). As a control (K), the substrate was used in the form of pure coconut water with a sugar content of 3%. From the research results it was found that Control (K) produced a yield of 76.9%, P1 of 53.7%, P2 of 62.2%, and P3 of 45.7%, however the results of statistical tests stated that the difference in these values ​​was not significant. The results of the nata de coco thickness test showed that Control (K) produced nata with the highest thickness (11.4 mm), while P2 produced the higher thickness (8.8 mm) compared to other treatments that used a mixture of coconut water and skimmed coconut milk as a substrate (P1 and P3). The results of the hedonic test showed that differences in sugar content (P1, P2, P3) did not have a significant effect on the liking value of the nata de coco produced, where all values ​​were in the